(untitled) (Malaysian Journal of Learning and Instruction, 2017)
Purpose – Student motivation for positive academic outcome and persistence at school is significantly affected by personal and environmental factors. Anchored in self-determination theory, this study tested a motivational model which looked at how support in terms of perceived teacher autonomy and from school administration constituted the key factors in explaining school climate. The study was also primarily concerned with how these crucial factors would help predict student motivation and perceived competence, and how they in turn, would affect student school performance and helped predict student drop out intentions. Methodology – This model was tested on 277 first year vocational college students in Hanoi, Vietnam. Data was collected through a self-report questionnaire. The hypothesized relationships were tested using partial least squares (WarpPLS 3.0). Findings – The structural model analysis carried out suggested that all the hypothesized relationships were statistically significant. Student experience of autonomy support from teachers and administrators predicted motivation and perceived competence, which in turn predicted student school performance and intentions to drop out from school. Value – The findings and its implication were discussed in relation to the type of teacher classroom behaviour and the nature of school administration style that would be required to facilitate autonomy support for the students to enhance their motivation and helped them gain competence.